Serial TIL infusions and PD-1 blockade drive long-term clonal persistence in prostate cancer - Arruda, Lucas C. M.; Karbach, Julia; Kiselicki, Dragan; Brand, Kathrin; Wahle, Claudia; Sinelnikov, Evgueni; Gustavus, Dirk; Hoffmeister, Hans; Atmaca, Akin; Jäger, Elke (Frontiers in Oncology, 2025)
Adoptive cell therapy using tumor-infiltrating lymphocytes (TIL) can achieve durable responses in patients with metastatic cancers, but the long-term clonal dynamics after multiple administration and synergy with checkpoint blockade remain understudied. We present a longitudinal case study of a patient with treatment-refractory metastatic prostate cancer that achieved complete and durable tumor remission over 5-years after multiple TIL infusions and anti-PD-1 therapy. We performed longitudinal high-throughput T-cell receptor (TCR) sequencing on blood and tumor samples collected over five years to track the persistence and dynamics of TIL-derived and endogenous clonotypes. TIL-derived clonotypes exhibited sustained persistence in blood, with notable clonal expansions correlating with reduced repertoire diversity, increased clonality, and observed clinical response. Multiple TIL administration increased the patient exposure to the therapy, improving its pharmacokinetics profile over time. The third TIL infusion was followed by pembrolizumab administrations, which coincided with the re-expansion of TIL-derived clonotypes and emergence of novel clones. Serial tracking revealed clonotype stability for up to five years post-treatment. Our findings provide insights into the long-term persistence and reactivation of TIL-derived immunity and illustrate the potent synergy between adoptive transfer and PD-1 blockade by enhancing both infused and endogenous tumor-reactive T cell responses, and supporting the integration of longitudinal immunogenomic monitoring in personalized immunotherapy.